PENGARUH MODEL PROBLEM BASED LEARNING BERBASIS MEDIA ULAR TANGGA TERHADAP HASIL BELAJAR PESERTA DIDIK PADA MATA PELAJARAN PPKN DI KELAS IV SD - Zahwa Adinda, Aulia; Kaulan Karima, Muhammad; Khairani, Fadhilah; Destini, Frida (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the effect of implementing the Problem Based Learning (PBL) model based on snakes and ladders media on the learning outcomes of fourth-grade elementary school students in PPKn. The research problem arises from the low learning outcomes of students caused by a teacher-centered learning process, the lack of variety in the use of models and learning media, and the low active involvement of students. The research uses a quantitative approach with a quasi-experimental design thru a non-equivalent control group design. The research population consisted of 47 students using purposive sampling techniques, including class IV A as the control class (25 students) and class IV B as the experimental class (22 students). Data were collected thru learning outcome tests and observation sheets, then analyzed using simple linear regression tests. The research results show that the application of the Problem Based Learning model based on the snakes and ladders media significantly affects the improvement of students' PPKn learning outcomes. These findings contribute to the development of PPKn learning in elementary schools thru the utilization of problem-based learning models combined with educational game media to enhance student engagement and learning outcomes.